Gambaran Sikap Remaja di Madrasah Aliah Putri Al-Islahuddin Kecamatan Kediri Lombok Barat Tentang Prilaku Seksual Beresiko - Marlina Riskawaty, Heny; Ernawati, Ernawati; Rispawati, Baik Heni; Bahtiar, Heri (Jurnal Ilmiah STIKES Yarsi Mataram, 2021)
Efforts to have reproductive life a healthy and responsible, means anyway or efforts to improve the quality of a teenager because ripeness alat-alat reproduction teenagers are an important part in the life of a teenager.Kind of risk reproductive health to deal with a juvenile between other, sexual violence sexually transmitted diseases(pms) infected with HIV/AIDS pregnancy and abortions.Based on survey UNFPA and BAPPENAS years 2009, as many as percent of the perpetrator 30 persen to 2 million abortions carried out by a teenager, while of the health ministry in march 2009, as many as percent of 54,3 17 thousand people living with aids was a teenager.In the last years 3 obtained the data that some students who experienced tanda-tanda sexually transmitted disease (PMS) .Purpose this research is to know an image of an attitude of a teenager at the Madrassa Aliyah doughter Al-Islahuddiny subdistrict Kediri Central Lombok about risk sexual behavior. Type this research is the observational descriptive.The sample technique used in this research is total sampling,with the number of respondents 151 one.Instruments gather statistic using a questionnaire and the analysis using fisher.based on research, in the for the respondents who have a good manners of sexual behavior and respondents ( 55 % 91,7 ), while the and having a on sexual behavior and respondents ( 5 % 8,3 ) .Researchis hoped can be effort to improve reproductive health status in responding to sexual behavior at risk and can assist in preventive.